Faktor-faktor Yang Mempengaruhi Minat Investasi Mahasiswa Pada Pasar Modal Di Kota Batam - Putri, Yehesy Pernanda; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2024)
This research aims to determine the magnitude of the influence or relationship between Investment Knowledge, investment risk and investment returns on the capital market in Batam City. Before entering the world of investment or capital markets, knowledge about investment is required, including an understanding of the potential risks and profits associated with investment. This research uses quantitative research with the type of replication research and uses a total of 329 respondents with non-probability sampling techniques and purposive sampling methods in sampling techniques where respondents only focus on management study program students at Putera Batam College and Riau Islands College. Data was also taken from journals, books and distributing questionnaires to predetermined respondents. With the help of the SPSS version 26 program, the results were obtained that investment information factors, speculation opportunities and speculation returns influence student speculation premiums in the capital market in Batam City